Cements with supplementary cementitious materials for high-temperature geothermal wells. (July 2020) - Pyatina, Tatiana; Sugama, Toshifumi
Highlights: Pozzolans help to hydrothermally self-heal damaged cementitious composites at 300 °C. Different hydrates participate in strength recovery and cracks sealing. Fly ash F improves cements' strong acid resistance (pH 0.2) at 90 °C. Micro-glass fibers allow reconstruction of fragmented samples for some formulations. Young's modulus can be used to classify cements failure type linked to cracks size. Abstract: This paper discusses self-healing ability, characterized by the strength recovery and crack sealing, thermal shock and acid resistance of several cementitious composites in water, alkali carbonate or geothermal brine at 300 °C. The tested formulations included a common high-temperature OPC/SiO2 formulation, a calcium-aluminate cement with alkali activated FAF blend (TSRC), alkali-activated granulated blast furnace slag (GBFS/SiO2 ) and fly ash C/fly ash F (FAC/FAF) cementitious blends. Compressive strength recoveries and visual observations of cracks sealing using 3D imaging after the compressive damage and then after the 5-day healing period were used to evaluate the self-healing abilities of these composites. The strength recoveries were evaluated for composites after 1-, 5-, 10-, 15-, and 30- day initial curing periods at 300 °C and after repeated damage and 5-day healing treatments. The nature of the failure was classified depending on the Young's modulus (YM) of the tested blends. Composites with moderate values of YM, such as OPC/SiO2 and TSRC developed slim cracks while brittle and very brittle FAC/FAF and GBFS/SiO2 cementitious blends produced multidirectional cracks or near-fragment failures resulting in poor strength recoveries. In comparison with the common high-temperature OPC/SiO2 blend, composites with alkali activated pozzolanic materials demonstrated a decrease in crack size during the short healing periods. Fly ash-containing composites showed better acid resistance surviving 28 days in sulfuric acid (pH 0.2) at 90 °C. The TSRC demonstrated the best thermal shock resistance losing only about 20 % of the original strength in five 350 °C heat→25 °C water thermal cycles. In all the tests the TSRC outperformed the rest of the composites with average strength recoveries of more than 85 %. Alkali carbonate was the most favorable for both strength recovery and crack sealing. The short-term strength recoveries could be further improved to above 100 % by addition of micro-glass fibers (MGF). However, the MGF raised the brittleness of the samples after longer initial curing times, which decreased recovery rates of the aged samples. Crystalline phase analysis demonstrated that different products assisted in strength recoveries and crack sealing. The later included for the most part silica and analcime while the former were hydrogrossulars (ferrian) with various stoichiometries, iron-magnesium minerals, cancrinite, quartz and boehmite. These phases formed thanks to the slow high-temperature alkaline reactions of fly ash and glass fibers for MGF-modified samples.